The Role of Democratic Values on Respect for Other People's Opinions in the Civic Education Learning Process - Syukur Kasieli Hulu; Kosmas Dohu Amajihono (Universitas Muhammadiyah Enrekang, 2023)
The value of democracy is a pattern of beliefs or good things that are used as guidelines for life for the community to realize a democratic life. One of the indicators of democratic values and also the focus of this research is the attitude of respecting opinions. Respect for other people's opinions is an attitude in which a person has respect and is able to accept any differences that exist without seeing who and what other individuals have. Formulation of the problem How is the role of democratic values in respecting the opinions of others in the learning process of civic education. What are the obstacles in instilling democratic values in respecting other people's opinions in the learning process of civic education. The purpose of the research was conducted to determine the role of democratic values in respecting the opinions of others, and to identify obstacles in instilling democratic values in respecting the opinions of others in the learning process of civic education. This research uses qualitative research with a description method. Data collection techniques are interviews, observation, and documentation. The results of the study revealed that the role of democratic values in respecting the opinions of others in the learning process of civic education is: 1) Students uphold other people's opinions, 2) Students heed other people's decisions or opinions, and 3) Students do not consider themselves the most correct. The obstacles in instilling democratic values in respecting the opinions of others in the learning process of civic education are the lack of student motivation in the learning process and ineffective communication between students in expressing opinions.